Minnowknits, too : more uncommon knits for kids, big and small - Eaton, Jil, 1949- (New York : Clarkson Potter Publishers, 1998)
Internationally acclaimed designer Jil Eaton has again put simple design and style into children s hand knits. In MinnowKnits, Too, she s created twenty-six innovative patterns using her signature bold colors, chic styling, and spirited details. From sweaters to rompers, bibs to bunting, here are one-of-a-kind outfits for kids of all ages and knitters of all skill levels. Illustrated with full-color photographs, drawings, schematics, and clear step-by-step instructions, MinnowKnits, Too brings bright looks and a fresh attitude to knits for kids.
"A MinnowKnits book."
Includes bibliographical references (p. 171) and index.
Keywords: Knitting -- Patterns; Children's clothing; Authors, American -- Maine